1997
DOI: 10.1006/viro.1997.8893
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Herpes Simplex Virus Type 1 L-Particles on Virus Entry, Replication, and the Infectivity of Naked Herpesvirus DNA

Abstract: Herpes simplex virus type 1(HSV-1) L-particles are known to be composed mainly of envelope and tegument proteins, to lack the nucleocapsid, and to be noninfectious. Thus L-particles represent interesting vaccine candidates. L-particles at > 1000/cell interfered with HSV-1 virion adsorption and penetration While L-particles did not affect HSV-1 growth kinetics in resting or nonresting BHK cultures infected with purified virions, treatment with L-particles before, or after, transfection with HSV-1 DNA resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…In fact, HSV-1 mutants that lack ICP0 function are significantly crippled in escaping latency and in initiating the lytic gene expression cascade [26]. Moreover, Dargan and Subak-Sharpe found ICP0 to be a major component of HSV-1 light-particles (Lparticles) and demonstrated that these smooth-membrane bound inclusion vesicles enhance viral infectivity and gene expression [27], whereas L-particles generated from ICP0 null HSV-1 mutants were unable to enhance viral gene expression and plaquing efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, HSV-1 mutants that lack ICP0 function are significantly crippled in escaping latency and in initiating the lytic gene expression cascade [26]. Moreover, Dargan and Subak-Sharpe found ICP0 to be a major component of HSV-1 light-particles (Lparticles) and demonstrated that these smooth-membrane bound inclusion vesicles enhance viral infectivity and gene expression [27], whereas L-particles generated from ICP0 null HSV-1 mutants were unable to enhance viral gene expression and plaquing efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Dargan and Subak-Sharpe have dissected the functional significance of several HSV-1 proteins found within L particles. ICP0 and VP16, when harbored within L particles that are added at the time of transfecting naked HSV-1 genomes, exhibit the most significant titer-enhancing effects, while VP11/12, VP13/14, and vhs show lesser impact on titers [27]. Our work further implicates ICP0 as a key component of helper virus-free HSV-1 amplicon particles, but does not rule out the importance of other passenger proteins in virion stability and expression competence, whether they are derived from an HSV BAC or the packaging cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Of major significance among them is the fact that L particles seem to behave like virions with regard to the processes of attachment, fusion, and release of functional tegument proteins into the cytoplasm of infected cells (8,24) and that these tegument proteins are active in enhancing the infectivity of both homologous and heterologous transfected alphaherpesvirus DNA (8). The biological competence of L particles, at least in cell cultures, has prompted several authors to propose that these virus particles boost successful initiation of the infectious process under adverse…”
mentioning
confidence: 99%
“…In the case of alphaherpesviruses, virions released from infected cells are the sole product of virus replication with the capacity to infect new cells and thus to maintain the virus in nature. Alphaherpesvirus virions consist of four distinct morphological components, each of them playing an important role in the infectious process: (i) an external lipid bilayer envelope that contains virus-encoded proteins essential for the attachment and fusion of the virus envelope with the plasma membrane of target cells (11,25,36); (ii) a characteristic layer (known as the tegument) consisting of proteins that are transferred into the cytosol immediately after virus entry and that enhance the ability of virions to initiate the process of infection (7,8,32); and (iii) an icosahedral capsid (consisting of 162 capsomers) that contains and transports (iv) a double-stranded linear DNA molecule up to the nuclear envelope, where the capsid interacts with the nuclear pore complexes to release the virus genome into the nucleus (15,27,32). After virus gene expression and DNA replication, progeny nucleocapsids assemble in the nucleus and reach the cytoplasm by envelopment followed by deenvelopment at the nuclear membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation